ANALISIS FAKTOR PEMBERIAN KREDIT KOPERASI WANITA AYU SARI KEPADA PEREMPUAN PEDESAAN DAN DAMPAKNYA TERHADAP KESEJAHTERAAN EKONOMI RUMAH TANGGANYA DI KABUPATEN TABANAN - Puspitadewi, Ni Luh Ketut Rai; Sri Budhi, Made Kembar (E-Jurnal Ekonomi dan Bisnis Universitas Udayana, 2016)
In the era of globalization in various development sectors, gender issues become a central issue, where women and men have the same treatment. Women are no longer dependent on men. Therefore, they have a desire to help the husband to meet the needs of their household by opening small businesses. Of efforts undertaken certainly, women need capital for smooth ness of their business es so women eager to seek credit through women cooperatives in Tabanan regency. At this time women cooperatives widely used by women as a place to help them in run ning their businesses like Koperasi Wanita Ayu Sari . This study uses SEM analysis Partial Least Square (PLS). The location of this study performed in Koperasi Wanita Ayu Sari . Kind of data used in this study are primary data. Data was collected through questionnaires to credit recipients women in Koperasi Wanita Ayu Sari . The population is the entire members of the women cooperative who obtain credit in Koperasi Wanita Ayu Sari , using census method with the number of respondents as many as 64 people. The analysis showed that , the socioeconomic status of credit recipients women and the role of women cooperatives significant ly affect on household's economic welfare, and social economic status of credit recipients women significant ly affect on the role of koperasi wanita Ayu Sari . In the study, there was in direct effect of socio-economic status of the recipient towards household's economic welfare through the role of women cooperatives. So that the role of cooperatives can improve welfare through the provision of credit koperasi Wanita Ayu Sari
Keywords: Socioeconomic status, women cooperatives, welfare